A Netnography and Contemporary Islamic Family Law Studies on the Controversy of Period Sex Trends on Social Media Twitter (X) - Auliya Ghazna Nizami; Muhammad Haidar (Indonesian Journal of Law and Islamic Law (IJLIL), 2024)
This study discusses the conversations of cyber citizens, specifically the social media Twitter (X), about the phenomenon of menstrual sex trends and how Islamic family law responds to netizens' discussions about the trend.   This research is a normative-empirical legal research. The results of this study show at least two main findings. First, the form of netizens' responses to the thread raised by Andrea Gunawan (@catwomanizer) varies. The first group states that even with the help of a device that prevents menstrual bleeding during sexual intercourse, it does not abort haram. Another group's response stated otherwise, if women who have more potential to be disadvantaged have been declared to be close to zero risk, as long as there is consent from both parties, then sexual intercourse can be carried out. Meanwhile, many other groups responded to this trend by asking the thread owner again and showing a neutral attitude of not judging the arguments made by the account owner. Second, Islamic law has clarity of attitudes and rules related to sexual behavior. There are no exceptions regarding the rules of sexual intercourse during menstruation. Normatively, Islamic law states that women who are menstruating should not be approached by their partners. Approaching in this case means sexual intercourse with the meeting of two genitals. Even if it is under the pretext and excuse that medical risks have been dealt with with the presence of certain tools, it still does not invalidate the original law.